Analysis of 12-Dimensions of Patient Safety Culture at PKU Muhammadiyah Bantul Hospital (Plenary Accredited) - Saputra, Rahmana Febri; Dewi, Arlina; Kusuma Dewi, Dyah Tri; Urhmila, Mariska (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Hospital accreditation is a practice of systemically assessing hospital performance against accepted standards. Hospital accreditation can improve patient safety through the implementation of service standards and continuous service improvement through a patient safety culture. PKU Muhammadiyah Bantul Hospital received a score of 73.9% in 2015 when the accreditation was intermediate. This research aims to show the patient safety culture at the PKU Muhammadiyah Bantul Hospital, which has been plenarily accredited. This research is a quantitative study with a cross-sectional approach with a descriptive research design to show the value of 12 dimensions of patient safety culture at PKU Muhammadiyah Bantul Hospital, which is plenarily accredited. The research subjects were 77 nurses and midwives who worked in the non-intensive care room at PKU Muhammadiyah Bantul Hospital based on inclusion and exclusion criteria. Nine dimensions got good grades, namely the dimensions of supervision, organizational learning, teamwork within units, openness and communication, feedback about errors, response to errors, management support, teamwork across units, handoffs, and transitions. Sufficient grades were obtained in the dimensions of perception, frequency of reports and staff/employees. The patient safety culture at PKU Muhammadiyah Bantul Hospital, when it received plenary accreditation, was classified as good (average score of 76.82%).